Rehabilitation of children with cerebral palsy and epilepsy: an assessment of the effectiveness and safety - E. A. Bukreeva; T. A. Sednenkova; E. Yu. Sergeenko; N. V. Chebanenko; K. V. Osipova; O. A. Laisheva; I. A. Shavyrin; A. G. Prityko; D. V. Kovalev; V. P. Zykov; P. L. Sokolov; P. A. Romanov (Лечащий Врач, 2021)
A study of the clinical effectiveness of the method of plantar pneumostimulation in the rehabilitation of 82 children with spastic and atonic-astatic forms of infantile cerebral palsy, aged 11 months to 17 years, suffering from symptomatic epilepsy, was carried out. When using the assessment of dynamics using the GMFM-66 and GMFCS scales, positive dynamics in motor status was revealed, which turned out to be significant in the younger age group. The authors believe that the reason for this phenomenon is the application of proprioceptive-corrective action in the case of an incomplete process of neuroontogenesis, which allows the maximum use of the reserves of the child's plastic brain. All children underwent an electroencephalographic study before and after the course of plantar pneumostimulation, and in none of the cases there was no clinical or neurophysiological exacerbation of the epileptic process. A conclusion is made about the effectiveness and epileptological safety of the plantar pneumostimulation technique, which allows us to recommend it for widespread implementation in neurorehabilitation practice.